Chylothorax as a problem in thoracic and cardiac surgery. Part II. Treatment. The proceedings algorithm - Rokicki, Wojciech; Rokicki, Marek; Filipowski, Marek; Wojtacha, Jacek; Zygo, Agnieszka (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Untreated chylothorax can lead to severe methabolic disturbances, inanition, lowered immunity and even death in a short period of time. Two methods of treatment are recommended – conservative or surgical and/or combination of both methods. The treatment of jatrogenic chylothorax gives 80-100% positive results. Authors based on clinical experience and review of the literature suggest introducing the own proceedings algorithm in patients with chylothorax of different origin.